2020
DOI: 10.17784/mtprehabjournal.2017.15.481
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality in the rehabilitation of the balance in the elderly.

Abstract: Introduction:Aging is characterized by a series of changes and adaptations that occur in the body progressively and irreversibly over the years. One of the consequences of senescence is the deficit of maintaining balance, this fact is explained by the involvement of the visual, somatosensory and vestibular systems. Given this scenario, the use of tools that can minimize these declines is of paramount importance. In recent times a resource that has been investigated is virtual reality, this technique stands out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These processes can be increased with IVR technology, since multisensory stimulation is greater and can enable better sensorimotor integration of the proposed tasks [24]. Several systematic reviews have shown the potential of VR tools to improve physical and functional abilities in older people, including strength, gait and balance [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…These processes can be increased with IVR technology, since multisensory stimulation is greater and can enable better sensorimotor integration of the proposed tasks [24]. Several systematic reviews have shown the potential of VR tools to improve physical and functional abilities in older people, including strength, gait and balance [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual difference between the two groups was minimal [ 4 ]. In addition, AR-based exercise in groups with significantly reduced balance, such as the older people, stroke, and Parkinson’s disease, showed as much improvement in gait and balance as the therapist [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research has focused on technology-based interventions and their potential to reduce fall risk in older adults. Options have included video classes of programmes such as the OEP [22], true virtual reality or home-based virtual reality programmes [23][24][25] and commercially available interactive videogaming programmes, known as exergaming [26]. The Wii Fit Balance Board (WBB) is an example of the latter.…”
Section: Introductionmentioning
confidence: 99%